Football`s Hilbert problems - Schatz, A. (Journal of Quantitative Analysis in Sports, 2005)
David Hilbert was a mathematician who in 1900 delivered the most influential speech in the history of mathematics (Hilbert 1902). He outlined 23 major problems to be studied in the next century, while outlining a philosophy for how mathematics should be studied. In the 2000 edition of Baseball Prospectus, Keith Woolner wrote an essay entitled "Baseball`s Hilbert Problems."(Kahrl, et al. 2000) Woolner`s essay, in the spirit of Hilbert, listed 23 unanswered questions about baseball. If baseball research is now about where David Hilbert was in 1900, football research is about where the Arabs were when they invented algebra. Analysis in football has a long way to go. The football Hilbert Problems do not merely consist of questions that need to be answered. They start with problems collecting the data that would help answer those questions.